Exact transient photon correlation with arbitrary laser pulses - Ooi, Chong Heng Raymond (American Physical Society, 2011)
We present a full quantum theory to study the transient evolution of photon pairs. We introduce a method which gives exact time-dependent solutions of the coupled quantum Langevin equations for a multilevel quantum particle driven by arbitrary time-dependent laser fields. The analytical solutions are used to develop a numerical code for computing exact time evolution of the two-photon correlation function. We analyze the effects of laser pulses sequence, pulse duration, chirping, and initial internal quantum states on the nonclassicality of the photon correlation through the violation of the Cauchy-Schwarz inequality. The results provide a promising possibility of controlling the generation of highly correlated photon pairs using tailored short laser pulses.